Gas drainage and utilization in coal mines in China: History, technological advances, and prospects - Guofu LI; Chao LI; Bichuan ZHANG; Yun XU; Zheng WANG; Xianjun ZHOU (Meitian dizhi yu kantan)
Objective and Methods To promote the research and application of gas drainage and utilization technologies for coal mines, this study systematically summarizes the history of China’s coal mines transitioning from gas pumping to gas drainage, the accurate and effective gas drainage technologies for typical coal mining areas in China, and the latest applications of technologies related to safe gas gathering and transportation, as well as the utilization of gas with a full range of concentrations. This study aims to provide a reference for accelerating the advancement in gas drainage and utilization technologies for coal mines, achieving methane emission reduction, and helping attain the goals of carbon neutrality and peak carbon dioxide emissions. Advancement The period from the 1930s to the 1950s represents the initial stage of gas pumping in coal mines in China. During this period, underground drilling was employed for gas pumping in target coal seams and their upper adjacent strata to ensure mining safety in the Fushun mining area in Liaoning Province, the Yangquan mining area in Shanxi Province, and the Tianfu mining area in Chongqing City. From the 1960s to the 1970s, gas pumping while mining was used for the prevention and control of gas overrun and accidents in the Jixi and Shuicheng mining areas in Heilongjiang and Guizhou provinces, respectively, achieving encouraging results. During this period, gas pumping technology for adjacent strata was developed, and methods including hydraulic slotting, controlled pre-splitting blasting, and water jet reaming were tested for coal seams with low air permeability. From the 1980s to the end of the 20th century, with a substantial increase in the gas outflow from the mining face, pressure-relief gas was effectively drained using various methods including gas pre-drainage in target coal seams, as well as gas pumping in adjacent strata and goaves. However, this period witnessed slow advancement in gas utilization. Since the beginning of the 21st century, the understanding of gas in coal mines has transitioned from simple disasters to disasters associated with resources, gradually achieving the transformation from gas pumping to gas drainage. In combination with the differences in geological conditions of gas in varying mining areas, three typical gas drainage modes have been formed: the surface-underground combined gas drainage mode through “four-zone linkage” in the Jincheng mining area in Shanxi Province (the new Jincheng mode), the protective layer mining mode for broken-soft and low-permeability coal seams in the Huainan-Huaibei area in Anhui Province (the Huainan-Huaibei mode), and the hydraulically enhanced permeability mode of the Songzao mining area in Chongqing City (the Songzao mode). Concurrently this period has seen the development and extensive applications of many safe transportation technologies and devices, including water sealing of fire barriers and explosion venting devices, dry flame arresters, and explosion suppression devices through water mist/automatic powder spraying. In terms of gas utilization, many technologies have been researched and applied, involving gas power generation, direct current (DC) oxidation, combustion in porous media, regenerative oxidation, and oxidation by mixing ventilation air methane with low-concentration gas. These technologies provide technical support for the utilization of gas with a full range of concentrations from coal mines. Nevertheless, gas drainage technologies for coal mines are confronted with challenges including poor applicability and high costs, and related gas drainage technologies suffer from low economic feasibility. Prospects Gas drainage and utilization technologies for coal mines will focus on the development of the advanced gas pre-drainage technology system for ten-year planning areas, the expansion of the simultaneous extraction of coal and gas mode, the optimization of gas utilization processes from the source, the improvement in the intelligent level of gas drainage pipeline networks, and the implementation of gas utilization projects via government-industry-university-institute collaborations. This will help achieve both the utilization of gas with a full range of concentrations from coal mines and the goals of carbon neutrality and peak carbon dioxide emissions in the coal industry.